Diet Quality and Physical Fighting Among Youth: A Cross-National Study - Jackson, Dylan B. (Journal of interpersonal violence, 2021)
The predictors of engaging in physical violence appear to be quite diverse, covering an array of social and psychological risk factors. The present study expands upon this literature by exploring the link between diet quality and physical fighting during early adolescence using cross-national data from the 2005/2006 Health Behaviors of School Children (HBSC) survey. The results reveal that the rate of physical fighting was 40% higher among youths with lower quality diets, whereas the odds of frequent physical fighting were 68% higher, relative to youths with better diets. Ancillary analyses reveal that (a) the link between diet quality and physical fighting was significantly larger among females and (b) significant associations between diet quality and physical fighting were detected in 38 of the 40 countries examined. Strategies designed to improve diet quality among youth may have the added benefit of reducing the likelihood of physical fighting and its negative sequelae.